“We went fishing in the dark”: a case report highlighting one therapeutic process in an out-patient comorbid anorexia nervosa (AN) and complex post-traumatic stress disorder (C-PTSD) treatment - Kathrine Rasch Moyo; Barbara Juliana Stenvall; Berit Støre Brinchmann (Journal of Eating Disorders)
Abstract Background There has been little research into effective treatment of comorbid AN and C-PTSD. This group of patients may show severe and enduring illness histories, often needing repeated hospitalisation and periods of outpatient treatment, adversely affecting their lives. Presently, there is no single recommended treatment for patients with comorbid AN and C-PTSD. Case presentation This article presents a case report of one therapeutic process through two stories; the patient’s and the therapist’s. The therapeutic approach in this case of comorbid AN and C-PTSD was symptomatic-, person- and process-oriented, with an eclectic choice of therapeutic methods including enhanced cognitive behavioural therapy for eating disorders (EDs) (CBT-E), mentalisation based therapy for EDs (MBT-ED), compassion focused therapy for EDs (CFT-E), emotionally focused therapy (EFT), and narrative exposure therapy (NET), aiming to provide personalised care; tailoring the interventions to the patient. The therapeutic relationship and treatment are analysed, with the aim of highlighting what influenced the therapeutic process. Conclusion The authors are not aware of other studies addressing the stories of patient and therapist in a therapeutic relationship, used to better understand factors relevant to the therapeutic process, in treating comorbid AN and C-PTSD. This case report provides insight into one therapeutic process treating these psychiatric illnesses in combination. The overall goal in therapy proved to be minimising the distances within the patient, between patient and therapist, between patient and society, and between the patient’s past and present, through a personalised approach. Further research should elaborate on the dyadic perspective unfolding from these two stories; addressing specifically the emotional-relational processes within the therapeutic relationship, to help broaden the understanding of treatment for comorbid AN and C-PTSD. We call for further research into personalised therapeutic interventions for these patients, suggesting a ‘toolkit‘ of interventions, tailored to the patient. It should not be the patient’s job to fit the method, but our job to make sure the method fits the patient.